Amelogenesis Imperfecta and Screening of Mutation in Amelogenin Gene - Fernanda Veronese Oliveira; Carla Vecchione Gurgel; Tatiana Yuriko Kobayashi; Thiago José Dionísio; Lucimara Teixeira Neves; Carlos Ferreira Santos; Maria Aparecida Andrade Moreira Machado; Thais Marchini Oliveira (Hindawi Limited, 2014)
The aim of this study was to report the clinical findings and the screening of mutations of amelogenin gene of a 7-year-old boy with amelogenesis imperfecta (AI). The genomic DNA was extracted from saliva of patient and his family, followed by PCR and direct DNA sequencing. The c.261C>T mutation was found in samples of mother, father, and brother, but the mutation was not found in the sequence of the patient. This mutation is a silent mutation and a single-nucleotide polymorphism (rs2106416). Thus, it is suggested that the mutation found was not related to the clinical presence of AI. Further research is necessary to examine larger number of patients and genes related to AI.